EP06 Successful treatment of alopecia universalis with rituximab therapy. (20th April 2020) - Oke, Anuoluwapo R; Young-Min, Steven
Abstract: Background: Alopecia universalis (AU) is a severe subtype of alopecia areata (AA), in which there is non-scarring hair loss affecting the whole body. The pathogenesis involves, increased MHC class I expression in hair follicles, loss of hair follicle immune privilege and autoimmune-mediated damage to pigmented hair. There is no cure for alopecia areata, and though mild cases may have a good chance of either spontaneous or treatment-induced recovery, the prognosis of complete hair loss is poor with less than 10% recovery. Treatment remains a challenge with no reliably effective therapy and in the absence of well-evaluated trials, isolated case reports can influence practice. Here, we present the first report of AU being successfully treated with rituximab with remarkably sustained improvement at 6 years follow up. This case is also the first report of AU developing in adult dermatomyositis (DM) and we speculate upon the implications for the aetiopathogenesis of both conditions. Methods: A 55-year-old lady, presented with proximal limb weakness, lethargy, a non-itchy rash, pleurisy and breathlessness. The serum creatinine kinase (3369 u/L) and anti-Jo-1 antibodies were elevated consistent with antisynthetase syndrome and a diagnosis of dermatomyositis was made. There was an initial response to corticosteroids and cyclophosphamide. She then relapsed and was treated with IV rituximab. Seventeen months after her initial presentation, she developed widespread hair loss sparing only white hairs (making Telogen Effluvium unlikely), combined with a concurrent relapse of her dermatomyositis. A diagnosis of alopecia universalis (AU) was made. A further course of IV rituximab therapy administered at this stage led to an excellent response in both her dermatomyositis and AU. At three months review, both the AU and the dermatomyositis had entered remission and this has been sustained 6 years on. Results: Please refer to the conclusion section. Conclusion: Disease activity in dermatomyositis has been linked with the expression of type I Interferon IFN and this may induce MHC class I expression that is identified on muscle biopsy. It may be that similar type I IFN action on hair follicles may have triggered the development of AU in our case. Whilst this is the first report of AU occurring with adult dermatomyositis, there has been a report of AU occurring in juvenile dermatomyositis. There are also other reports of other combinations of autoimmune conditions occurring with both DM & AU. This case also demonstrates that rituximab, an anti-CD 20 B cell therapy, maybe a useful treatment option in alopecia areata and universalis. This has not been reported elsewhere. Despite postulation that AU is a mainly T cell-driven disease, this case demonstrates that B cells may play a role, in much the same way that we now recognise the importance of B cell involvement in RA. Disclosures: A.R. Oke None. S. Young-Min None.